The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.chest.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Bacterial Bronchitis in Children

Abstract: PBB is associated with a future diagnosis of bronchiectasis in a subgroup of children. Lower airway infection with H influenzae and recurrent PBB are significant predictors. Clinicians should be cognizant of the relationship between PBB and bronchiectasis, and appropriate follow-up measures should be taken in those with risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…For example, we examined presence of H. influenzae as our earlier cohort study of children with PBB enrolled at the time of bronchoscopy identified that culturing H. influenzae in BAL fluid was a significant independent predictor (OR adj , 7.6; 95% CI, 1.7-34.3; P = .009) of being diagnosed with bronchiectasis within the next 2 years. 33 However, the absence of statistical significance may be related to our relatively small sample size. Also, BAL neutrophil counts may not be sensitive enough (compared to other downstream markers like IL-1β) to differentiate the degree of airway neutrophilia between subjects.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, we examined presence of H. influenzae as our earlier cohort study of children with PBB enrolled at the time of bronchoscopy identified that culturing H. influenzae in BAL fluid was a significant independent predictor (OR adj , 7.6; 95% CI, 1.7-34.3; P = .009) of being diagnosed with bronchiectasis within the next 2 years. 33 However, the absence of statistical significance may be related to our relatively small sample size. Also, BAL neutrophil counts may not be sensitive enough (compared to other downstream markers like IL-1β) to differentiate the degree of airway neutrophilia between subjects.…”
Section: Discussionmentioning
confidence: 87%
“…We chose these factors based on biological plausibility and/or published data. For example, we examined presence of H. influenzae as our earlier cohort study of children with PBB enrolled at the time of bronchoscopy identified that culturing H. influenzae in BAL fluid was a significant independent predictor (OR adj , 7.6; 95% CI, 1.7‐34.3; P = .009) of being diagnosed with bronchiectasis within the next 2 years . However, the absence of statistical significance may be related to our relatively small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…These endotypes are clinically relevant as those with PBB-extended are more likely to have tracheo-bronchomalacia [34] and those with recurrent PBB are more likely to have subsequent diagnosis of bronchiectasis. [35]…”
Section: Diagnosismentioning
confidence: 99%
“…This may be associated with bronchiectasis in a subgroup of children with Haemophilus influenzae infection or recurrent episodes,12 and these children require particular attention. Persistent moist cough is a hallmark of bronchiectasis, and can be either idiopathic or due to disorders such as immunodeficiency, aspiration syndromes, cystic fibrosis, or primary ciliary dyskinesia 13…”
Section: What Underlying Causes Should I Consider?mentioning
confidence: 99%